Transient Inactivation of the Medial Prefrontal Cortex and Ventral Hippocampus Impairs Active Place Avoidance Retrieval on a Rotating Arena - Cernotova, Daniela; Stuchlik, Ales; Svoboda, Jan (Frontiers in Neural Circuits, 2021)
It is well known that communication between the medial prefrontal cortex (mPFC) and the ventral hippocampus (vHPC) is critical for various cognitive and behavioral functions. However, the exact role of these structures in spatial coordination remains to be clarified. Here we sought to determine the involvement of the mPFC and the vHPC in the spatial retrieval of a previously learned active place avoidance task in adult male Long-Evans rats, using a combination of unilateral and bilateral local muscimol inactivations. Moreover, we tested the role of the vHPC-mPFC pathway by performing combined ipsilateral and contralateral inactivations. Our results showed not only bilateral inactivations of both structures, but also that the combined inactivations impaired the retrieval of spatial memory, whereas unilateral one-structure inactivations did not yield any effect. Remarkably, muscimol injections in combined groups exerted similar deficits, regardless of whether the inactivations were contralateral or ipsilateral. These findings confirm the importance of these structures in spatial cognition and emphasize the importance of the intact functioning of the vHPC-mPFC pathway.